(untitled) (Bangladesh Journal of Zoology, 2022)
Fourteen various fish samples i.e., rui Labeo rohita, catla Gibelion catla, striped dwarf catfish Mystus vittatus, stinging catfish Heteropneustes fossilis, walking catfish Clarias batrachus, Ganges river sprat Corica soborna, mola carplet Amblypharyngodon mola, common carp Cyprinus carpio, Nile tilapia Oreochromis niloticus, climbing perch Anabas testudineus, spotted snakehead Channa punctatus, striped snakehead Channa striata, bronze featherback Notopterus notopterus, wallago catfish Wallago attu and mixed juvenile prawns were collected from a pond of closed down DDT (Dichlorodiphenyltrichloroethane) factory area of Chittagong Chemical Complex (CCC) of Bangladesh to assess the concentrations of DDT and its metabolites (4,4’-DDD and 4,4’-DDE). The fish flesh and shell-free prawn muscle samples were extracted by QuEChERS method and these were cleaned up using H2SO4. The cleaned sample extracts were analyzed using a Gas Chromatograph coupled with Electron Capture Detector (GC-ECD). The cultured L. rohita was used as a control which was found to contain no detectable amount of DDTs. Recovery experiments with control samples were spiked with certified DDTs standard at three different concentrations (0.01 mg kg-1, 0.02 mg kg-1 and 0.05 mg kg-1) levels. The percent recoveries were 72-114 % (0.05 mg kg-1), 70-101 % (0.01 mg kg-1) and 87-105 % (0.02 mg kg-1). LOD and LOQ of the standards were found to be 0.0625 μg kg-1 and 0.2063 μg kg-1, respectively and R2 of 4’-DDE, 4,4’-DDD, 2,4’-DDT and 4,4’-DDT were found to be 0.999, 0.999, 0.999 and 0.998, respectively. The concentrations of total DDTs residue in fish and prawn samples ranged between 0.66 ng g-1 in W. attu to 8.90 ng g-1 in H. fossilis. The ratios of 4,4’-DDT/ΣDDTs in the studied fish samples indicated the historical use of DDTs in the adjacent region around the DDT factory of the CCC area. The concentrations of total DDTs in all the samples were within the permissible Maximum Residue Level (MRL) recommended by FAO-WHO. To assess human health risks, Health risk Indexes (HI) of fish and prawn samples were calculated. HIs<1 in all fish and prawn samples indicated that the fish samples are safe to consume but the daily consumption of the fish together with other contaminated food may cause human health hazards. Bangladesh J. Zool. 49 (3): 381-391, 2021